2cosx*(sinx+1)=0

Simple and best practice solution for 2cosx*(sinx+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2cosx*(sinx+1)=0 equation:


Simplifying
2cosx(sinx + 1) = 0

Reorder the terms:
2cosx(1 + insx) = 0
(1 * 2cosx + insx * 2cosx) = 0

Reorder the terms:
(2cinos2x2 + 2cosx) = 0
(2cinos2x2 + 2cosx) = 0

Solving
2cinos2x2 + 2cosx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '2cosx'.
2cosx(insx + 1) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'cosx' equal to zero and attempt to solve: Simplifying cosx = 0 Solving cosx = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cosx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(insx + 1)' equal to zero and attempt to solve: Simplifying insx + 1 = 0 Reorder the terms: 1 + insx = 0 Solving 1 + insx = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + insx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + insx = 0 + -1 insx = 0 + -1 Combine like terms: 0 + -1 = -1 insx = -1 Add '-1insx' to each side of the equation. insx + -1insx = -1 + -1insx Combine like terms: insx + -1insx = 0 0 = -1 + -1insx Simplifying 0 = -1 + -1insx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4x+6x-12x= | | 5sin^2*x+4sin*2x+6cos^2*4x=2 | | z=3x+6 | | h(t)=-16t^2+175+500 | | z=3x+2y-4 | | 5sin^2*x+4sin*2x+6cos^2*4x=0 | | 3/18=1/6 | | 3/1=1/6 | | 3=2j+1 | | 53+14y-8+13y=180 | | 4f-8f+7f= | | (F)x=4x+7 | | -21=q-8 | | x^4-10x^3+37x^2-24=0 | | -2x+16=4 | | 4x-17=3x-24 | | y+y^2=8 | | x=2(8)+2 | | 6d+7=3d+31 | | x^2-16x+220=0 | | t=3x+2y | | x=2(5)+3 | | x=-8(25)+200 | | c=x+y | | 120=-8x+200 | | 6(x-3)=2(x+3) | | x=5(10)+2 | | 5x-7=25-3x | | 5+2=10 | | 14-3x=-x+4 | | 4y-10+y+47=7y+40-5y | | 9*0.89*2x=96 |

Equations solver categories